Perencanaan Pengelolaan Kawasan Konservasi Berbasis Pemberdayaan Masyarakat (Studi pada Balai Taman Nasional Gunung Merapi Propinsi Daerah Istimewa Yogyakarta) - Susanto, Andrian (Jurnal Ilmiah Administrasi Publik, 2016)
Referring to the vision of the Ministry of Forestry, vision NPMM Office isBecoming National Park Yang Settled in Managing Human Volcano Dynamic Based Participation of Parties, in which the management of NPMM takes the role of the participation of the parties, especially communities in creating plans that are participatory and collaborative, one size for assess the success of the performance can be seen from how NPMM Office planned community development programs in the villages around NPMM. The focus of this study is to determine how NPMM management planning related to community development activities. Results of this study concluded that the planning of community-based management of NPMM is not likely to procedural but substantive aspects already accommodated, already apply the principle of sustainable development. In the planning of community development activities have also been pursued in a participatory and collaborative, though still within the framework of fulfilling the social responsibility of the organization or the policy direction of the Ministry of Environment and Forestry.